Analisis Kesulitan Belajar Bahasa Arab: (Studi di MTs. N. 1 Bandar Lampung) - Faturahman Fuadi (LP2M IAIN Sultan Amai Gorontalo, 2019)
The purpose of this study is to find out and describe the difficulties of students in learning Arabic. This type of research is qualitative research. The results showed that first, the lack of interest and motivation of students to learn Arabic, second, the difficulty of students in reading and understanding the meaning of each Arabic vocabulary, third, parental attention to students' Arabic learning outcomes is lacking, fourth, the method of delivering material is still monotonous, the teachers only used the lecture method, finally, the use of learning media is less varied.